Characterisation of microorganisms used for the production of food enzymes. (11th June 2019) - ,; Silano, Vittorio; Barat Baviera, José Manuel; Bolognesi, Claudia; Brüschweiler, Beat Johannes; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Lampi, Evgenia; Mortensen, Alicja; Rivière, Gilles; et al.
Abstract: This document is intended to assist the applicant in the preparation and the presentation of an application, as foreseen in Article 17.3 of Regulation (EC) No 1332/2008, for the authorisation of food enzymes. It specifically covers the characterisation of microorganisms used as production organisms.